The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1186/1471-2288-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Total Design Method in a survey of Japanese dentists

Abstract: BackgroundThis study assessed the application of the Total Design Method (TDM) in a mail survey of Japanese dentists. The TDM was chosen because survey response rates in Japan are unacceptably low and the TDM had previously been used in a general population survey.MethodsFour hundred and seventy eight dentist members of the Okayama Medical and Dental Practitioner's Association were surveyed. The nine-page, 27-item questionnaire covered dentist job satisfaction, physical practice, and dentist and patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Notably, a study among Japanese dentists applying the Dillman Total Design Method and multi-modal survey delivery only achieved a 47% response rate in their population, compared to some surveys among dentists in the United States that had employed the Dillman approach to achieve comparably higher response rates, suggesting that portability may not apply in all settings. 20 A concern with respect to lower response rates is the increased risk of bias. While robust response rates are generally thought to provide a more accurate reflection of the larger population and minimize potential for bias, no definitive 'gold standard' response rate has been advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a study among Japanese dentists applying the Dillman Total Design Method and multi-modal survey delivery only achieved a 47% response rate in their population, compared to some surveys among dentists in the United States that had employed the Dillman approach to achieve comparably higher response rates, suggesting that portability may not apply in all settings. 20 A concern with respect to lower response rates is the increased risk of bias. While robust response rates are generally thought to provide a more accurate reflection of the larger population and minimize potential for bias, no definitive 'gold standard' response rate has been advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Data on procedure conversion rate were obtained in six studies,26,29,31,3840 which assessed 1,314 and 914 patients in chest port group and arm port group, respectively. The procedure conversion rate was significantly higher in arm port group than that in chest port group (2.51% in chest port group and 8.32% in arm port group; OR 0.27, 95% CI 0.15–0.46; p <0.001) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…As for operating time, three studies including 707 patients were reported, however, one study30 presented operating time as “mean ± standard deviation”, one study39 presented as “mean and range”, and the last one31 displayed as “mean and interquartile range”. Using Hozo’s26 method, ranges were converted to estimated SD for further comparison 41. Result of the analysis of operating time revealed that there were no statistically significant differences between chest port group and arm port group (WMD −4.31; 95% CI −17.81–9.19; p =0.53), with high between-study heterogeneity ( I 2 =0.98, p <0.01) (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Means were used for meta-analysis unless otherwise mentioned. If the mean was not reported by the author, the means or standard deviations were calculated as medians or ranges, respectively 22. The following data were extracted from each study: author, year, country, study period, study design, number of patients, age, gender, tumor size, mortality, morbidity, operation time, blood loss, blood transfusion, hospital stay, reoperation and long term survival including 3-year overall survival (3-OS) and 5-year overall survival (5-OS).…”
Section: Methodsmentioning
confidence: 99%